TINJAUAN YURIDIS TERHADAP TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA YANG DILAKUKAN OLEH ASISTEN RUMAH TANGGA TERHADAP MAJIKAN ( STUDI KASUS PUTUSAN NO.386/PID/KDRT/2013/PN.JKT.SEL ) - Purba, Boy Calvin; R, Mukhlis; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Karolina Renyaan, who works as a nurse to care for Nazarina, the parent of Novita Purnama Sari, has committed physical violence against Nazarina. From the results of post mortem et repertum No.M 08560 / b21030 / 2012-S8. One of the criminal acts regulated in Article 5 letter a of Law Number 23 of 2004 concerning PKDRT. Article 44 Paragraph 1 of Law Number 23 Year 2004 concerning PKDRT. The scope of household is regulated in Article 2 Paragraph 1 of Law Number 23 Year 2004 concerning the Elimination of Domestic Violence. However, what was stated in Decision Number 386/PID /KDRT/2013/PN.JKT.SEL judges in fact argued that the perpetrator had legally and convincingly violated Article 351 Paragraph 1 of the Criminal Code concerning Torture by imprisonment for 7 months.This type of research is normative juridical legal research, namely research conducted with literature review or literature study in search of data. This research is descriptive in nature which provides data that is as thorough and detailed as the existing problems. In this study using qualitative data analysis which means explaining and concluding about the data that has been collected by the author. This research uses secondary data or codified scientific data.The results of this study explain that the application of Article 351 paragraph (1) of the Criminal Code in this case is not correct, as regulated in the provisions of Article 63 of the Criminal Code, if an act falls under more than one criminal rule, only one of those rules will be imposed. if different, it shall contain the heaviest principal penalty. If a criminal act is included in a general criminal rule, it is also regulated in a special criminal rule, then the specific one is applied. In accordance with the principle of lex specialist derogate lex generalis, it is more appropriate to apply the provisions of Article 44 paragraph 1 of Law of the Republic of Indonesia No.23 of 2004 concerning PKDRT.Keywords. Juridical Review - Domestic Violence - Judgment